Hebb–Wagner polarization method for determining the oxygen ion conductivity in barium cerate-zirconate. Issue 13 (28th February 2022) - Miruszewski, T.; Dzierzgowski, K.; Winiarz, P.; Wachowski, S.; Mielewczyk-Gryń, A.; Gazda, M.
Abstract : Modified DC Hebb–Wagner polarization method was used to study oxygen ionic conductivity in BaCe0.6 Zr0.2 Y0.2 O3 . New measuring cell and calculation model proposed. Conduction mechanism of oxygen ions is influenced by protons in BaCe0.6 Zr0.2 Y0.2 O3 . Abstract : In this work, the partial conductivity of oxygen ions in BaCe0.6 Zr0.2 Y0.2 O3 was studied at different temperatures and water partial pressures. For this purpose, a modified DC Hebb–Wagner polarization method with an electrode blocking for protons and electrons was used. A new type of measuring cell as well as a suitable calculation model were proposed for the determination of partial oxygen ionic conductivity in materials with three mobile charge carriers, namely, oxygen ions, protons and electrons. The obtained oxygen ion partial conductivity ( σ O ) in the BaCe0.6 Zr0.2 Y0.2 O3 mixed protonic oxygen ionic–electronic conductor was 2.3 × 10 −3 S cm −1 at 800 °C and p O2 = 0.20 atm, p H2 O = 0.023 atm. This is in agreement with the literature reports and indicates the feasibility of this method for characterization of mixed-conducting ceramics with unknown oxygen ionic conductivity. The obtained results also indicate the influence of protons on the conduction mechanism of oxygen ions. This information may be very useful for the analysis of the interaction between the charge carriers in mixed conducting materials.